PERBEDAAN MOTIVASI MENYELESAIKAN SKRIPSI MAHASISWA BIMBINGAN DAN KONSELING YANG TINGGAL DI RUMAH DENGAN DI INDEKOS - Ayuningtyas, Bekti; Wibowo, Agus; Pranoto, Hadi (Universitas Muhammadiyah Metro, 2023)
Motivation to finishing thesis of students living in boarding houses and at home. Data collected from 51 guidance and counseling students. 15 of the students live in boarding houses, and 36 at home. Sampling using saturated sample technique. The variable that is measured is the motivation to complete the thesis using a questionnaire given to 51 students. Data analysis was carried out using a comparative quantitative approach. The average value of student’ motivation to finishing their thesis living in boarding houses is 86,73 and students living at home 94,61. It is known that the average value of the motivation to complete the thesis of students living at home is higher, and indicates that there are differences in motivation to finishing thesis between students live in boarding houses and at home. This is reinforced by the results of analysis calculations using the T test which shows that thitung > ttabel. (2,275 >2,00958 ) with a significance taeaf of 5%.That thus it is concluded hat Ho is rejected and Ha is accepted. Which means that there are differences in student motivation in finishing their thesis between students live at home for guidance and counseling students at Muhammadiyah University of Metro class of 2019 seen from their residence status.